The Finno-Ugric Peoples of the Middle Volga and Southern Urals Based on the 1920 All-Russian Census: New Data - Leyla F. Sayfullina (Финно-угорский мир, 2025)
Introduction. The relevance of the research is conditioned by the introduction into scientific use of a previously unused set of archival sources – farmstead cards of the 1920 agricultural census in Little Bashkiria, stored in the National Archive of the Republic of Bashkortostan, which have a significant potential for studying the history of the peasantry and ethno-demography of the region. The aim of the study is to clarify the number and determine the geographical areas of compact residence of the Finno-Ugric peoples (Mordovians, Mari, Udmurts) of the Middle Volga region on the territory of Little Bashkiria as of 1920 on the basis of a critical analysis of the primary census materials.